The temporal relationship between speech auditory brainstem responses and the acoustic pattern of the phoneme /ba/ in normal-hearing adults - Akhoun, I.; Gallégo, S.; Moulin, A.; Ménard, M.; Veuillet, E.; Berger-Vachon, C.; Collet, L.; Thai-Van, H. (Clinical neurophysiology, 2008)
To investigate the temporal relationship between speech auditory brainstem responses and acoustic pattern of the phoneme /ba/. Speech elicited auditory brainstem responses (Speech ABR) to /ba/ were recorded in 23 normal-hearing subjects. Effect of stimulus intensity was assessed on Speech ABR components latencies in 11 subjects. The effect of different transducers on electromagnetic leakage was also measured. Speech ABR showed a reproducible onset response (OR) 6 ms after stimulus onset. The frequency following response (FFR) waveform mimicked the 500 Hz low pass filtered temporal waveform of phoneme /ba/ with a latency shift of 14.6 ms. In addition, the OR and FFR latencies decreased with increasing stimulus intensity, with a greater rate for FFR (−1.4 ms/10 dB) than for OR (−0.6 ms/10 dB). A close relationship was found between the pattern of the acoustic stimulus and the FFR temporal structure. Furthermore, differences in latency behaviour suggest different generation mechanisms for FFR and OR. The results provided further insight into the temporal encoding of basic speech stimulus at the brainstem level in humans.